Analisis Pengaruh Wudhu Terhadap Relaksasi dan Stres: Studi Integrasi Agama dan Ilmu Psikologi - Zaleha, Siti; Risnawati, Risnawati; Yusrianto, Edi (UIR Press, 2025)
Stress is an increasing mental health problem and greatly affects various aspects of a person's life in this era of globalization. In religion, forms of spirituality have been shown to play an important role in helping individuals overcome emotional and mental stress, one of which is ablution. Based on this, the purpose of this study is to conduct an in-depth analysis of the effect of ablution on relaxation and stress with an integrated approach between religion and psychology. This study uses a qualitative descriptive approach with a literature review method. Data collection was carried out by collecting and analyzing various relevant scientific sources, including journals, books, and academic articles. The results of this study indicate that: 1) The effect of ablution on relaxation and stress greatly helps individuals in overcoming emotions and stress, 2) The form of integration of religion and psychology in the context of ablution is that ablution not only prepares individuals for worship, but also provides psychological benefits that can support relaxation and general well-being